2018
DOI: 10.1590/s1982-21702018000200017
|View full text |Cite
|
Sign up to set email alerts
|

Palsar-2/Alos-2 and Oli/Landsat-8 Data Integration for Land Use and Land Cover Mapping in Northern Brazilian Amazon

Abstract: In northern Brazilian Amazon, the crops, savannahs and rainforests form a complex landscape where land use and land cover (LULC) mapping is difficult. Here, data from the Operational Land Imager (OLI)/Landsat-8 and Phased Array type L-band Synthetic Aperture Radar (PALSAR-2)/ALOS-2 were combined for mapping 17 LULC classes using Random Forest (RF) during the dry season. The potential thematic accuracy of each dataset was assessed and compared with results of the hybrid classification from both datasets. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…With the fused approach, some familiar misclassifications for SAR (classes with similar surface backscatter patterns, i.e., roads, runways, still water or lawns) and optical (classes with similar spectral reflectance) data could be reduced. Some classes are difficult to detect using a spectral response from optical data or backscatter from the SAR instrument, but this might be easily distinguished by their combined use [26,104,105]. Although F1 and FoM metrics are more robust than UA and PA [75,106], UA values, as a measure of the reliability of the map, were visualized ( Figure 4) for each study area.…”
Section: Discussionmentioning
confidence: 99%
“…With the fused approach, some familiar misclassifications for SAR (classes with similar surface backscatter patterns, i.e., roads, runways, still water or lawns) and optical (classes with similar spectral reflectance) data could be reduced. Some classes are difficult to detect using a spectral response from optical data or backscatter from the SAR instrument, but this might be easily distinguished by their combined use [26,104,105]. Although F1 and FoM metrics are more robust than UA and PA [75,106], UA values, as a measure of the reliability of the map, were visualized ( Figure 4) for each study area.…”
Section: Discussionmentioning
confidence: 99%
“…Ullmann et al [90] examined the scattering characteristics from polarimetric data obtained at X-, C-, and L-band in a tundra-dominant ecosystem and found that L-band data were more appropriate to differentiate classes with low levels of vegetation cover. Pavanelli et al [39] integrated data from Landsat-8/OLI and ALOS/PALSAR-2 satellites and classified them in the RF algorithm, to map the LULC classes in a fragment located in the northern part of the Brazilian Amazon. They found that ALOS/PALSAR-2 data's most important contribution was the possibility to discriminate classes with low levels of biomass (grasslands and wooded savanna).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest a greater contribution of horizontally distributed components, such as fallen stems and branches in areas severely affected by fire. Recent studies focusing on multi-sensor analysis for LULC mapping and change detection in tropical regions [39,40] have used dual-polarimetric ALOS/PALSAR-2 images integrated with Landsat multispectral images. Pavanelli et al [39] highlighted the SAR potential to discriminate savannah-like vegetation in the Brazilian Amazon, with an improvement in OA of 6% in relation to the classification results obtained only from optical data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such actions need to take into consideration the inter and intra-pixel complexity in tropical landscapes, the loss of variables in the classifier models by attribute selection or by radiometric transformations intrinsic to the fusion of multi-source or multi-data. Therefore, scientific effort has been directed to the use of classifiers such as Random Forest that has been applied for both optical-based reflectance measures and SAR polarimetric-based texture metrics (Hagensieker et al 2018;Pavanelli et al 2018) to increase the accuracy level on LULC class stratification.…”
Section: Discussionmentioning
confidence: 99%